(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The article covers the events related to the transfer of meaning in artistic speech, the words used in the figurative sense in Uncle Murad’s story "Stars burn forever" are analyzed linguistically and the place and semantic properties of units in the text are explained. There are also relevant ideas about the types of meaning transfer.